2016
DOI: 10.1002/jhet.2660
|View full text |Cite
|
Sign up to set email alerts
|

(Substituted Ylidene)Amino‐2‐Oxo‐Indolylidene Thioureas and Bis(2‐Oxo‐Indolylidene)Urea from (Ylidene)Thiocarbonohydrazides and Isatylidene Malononitrile

Abstract: A simple and efficient synthesis of (substituted ylidene)(2‐oxoindolylidene)thiocarbohydrazones and bis(2‐oxoindolylidene)urea was achieved by the reaction of (substituted ylidene)thiocarbonohydrazides with isatylidene malononitrile. Rational for this conversation involving the nucleophilic additions on the dicyanomethylene carbon atom is presented. The structures of the products have been confirmed by using spectral and single‐crystal X‐ray analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Compound 6 was previously synthesized from the reaction of a 1:1 mixture of thiocarbohydrazide ( 2 ) and isatin ( 4 ) in boiling ethanol in the presence of acetic acid for 2 h . Also, 6 was produced as a side product (20–27% yield) from the reaction of isatylidene malononitrile and (ylidene)thiocarbohydrazides in ethanol in the presence of piperidine at room temperature .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 6 was previously synthesized from the reaction of a 1:1 mixture of thiocarbohydrazide ( 2 ) and isatin ( 4 ) in boiling ethanol in the presence of acetic acid for 2 h . Also, 6 was produced as a side product (20–27% yield) from the reaction of isatylidene malononitrile and (ylidene)thiocarbohydrazides in ethanol in the presence of piperidine at room temperature .…”
Section: Resultsmentioning
confidence: 99%
“…A mixture of 3 (0.50 g, 2.0 mmol) and 4 (0.59 g, 4.0 mmol) in dry EtOH (20 mL) containing AcOH (0.2 mL) was refluxed for 4 h. The solid obtained on cooling was filtered, dried, and recrystallized from DMF to give 6 as yellow crystals in 65% yield, mp 262–263°C (lit. mp 262–264°C ; 260–262°C ).…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that a mixture of 3‐{[(3 Z )‐2‐oxo‐2,3‐dihydro‐1 H ‐indol‐3‐ylidene]amino}‐1‐[( E )‐(substituted ylidene)amino]thiourea derivatives 15a – j (43–56%) and N′ ,2‐bis(2‐oxoindolin‐3‐ylidene)‐hydrazine‐1‐carbothiohydrazine ( 16 ) (20–31%), was effectively obtained by the reaction between (substituted‐ylidene) thiocarbonohydrazides 13a – j with isatin malononitrile ( 14 ) with stirring at r.t in absolute ethanol and few drops of piperidine (Scheme ) .…”
Section: Thiocarbohydrazidesmentioning
confidence: 99%